Effect of Total Quality Management Practices on Employees’ Work Related Attitudes in Nepalese Commercial Banks - Chaudhary, Binay (Nepalese Journal of Business, 2025)
This study examines effect of total quality management practices on employees’ work-related attitudes in Nepalese commercial banks. Employee’s performance and motivation is the dependent variable. Similarly, the selected independent variables are top management commitment, employee’s involvement, continuous improvement, employee’s education and training and customer focus. The study is based on the primary data with 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and effect of total quality management practices on employees’ work related attitude in Nepalese commercial banks on employee’s performance and motivation in Nepalese commercial banks. The study indicates that top management commitment is positively correlated to employee’s performance and motivation. It indicates that high top management commitment leads to increase the employee’s performance and motivation. Similarly, employee’s involvement is positively correlated to employee’s performance and motivation. It indicates that higher the employee’s involvement leads to increase the employee’s performance and motivation. Likewise, continuous improvement is positively correlated to employee’s performance and motivation. It indicates that continuous improvement mechanism leads to increase the employee’s performance and motivation. Further, employee’s education and training is positively correlated to employee’s performance and motivation. It indicates that higher the employee’s education and training, higher would be the employee’s performance and motivation. Moreover, customer focus is positively correlated to employee’s performance and motivation. It indicates that higher the customer focus leads to increase the employee’s performance and motivation.